Immersion Foot Syndrome in 6 Equids Exposed to Hurricane Floodwaters. Issue 2 (March 2020) - Taylor, Brianne M.; Chaffin, M. Keith; Hoffmann, Aline Rodrigues; Edwards, John F.; Arenas-Gamboa, Angela M.
Prolonged exposure to water, known as immersion foot syndrome in humans, is a phenomenon first described in soldiers during World War I and characterized by dermal ischemic necrosis. In this report, we describe the pathologic findings of a condition resembling immersion foot syndrome in 5 horses and 1 donkey with prolonged floodwater exposure during Hurricane Harvey. At necropsy, all animals had dermal defects ventral to a sharply demarcated "water line" along the lateral trunk. In 5 animals, histologic examination revealed moderate to severe perivascular dermatitis with vasculitis and coagulative necrosis consistent with ischemia. The severity of the lesions progressed from ventral trunk to distal limbs and became more pronounced in the chronic cases. The pathophysiology of immersion foot syndrome is multifactorial and results from changes in the dermal microvasculature leading to thrombosis and ischemia. Prompt recognition of this disease may lead to appropriate patient management and decreased morbidity.